METHODS OF CONTROLLING THE AVERAGE DIAMETER OF THE THREAD WITH ASYMMETRICAL PROFILE - L. M. Aliomarov; N. M. Vagabov; A. Z. Kurbanov (Вестник Дагестанского государственного технического университета: Технические науки)
To handle the threaded holes in hard materials made of marine machinery, operating at high temperatures, heavy loads and in aggressive environments, the authors have developed the combined tool core drill -tap with a special cutting scheme, which has an asymmetric thread profile on the tap part. In order to control the average diameter of the thread of tap part of the combined tool was used the method three wires, which allows to make continuous measurement of the average diameter of the thread along the entire profile. Deviation from the average diameter from the sample is registered by inductive sensor and is recorded by the recorder. In the work are developed and presented control schemes of the average diameter of the threads with a symmetrical and asymmetrical profile. On the basis of these schemes are derived formulas for calculating the theoretical option to set the wires in the thread profile in the process of measuring the average diameter. Conducted complex research and the introduction of the combined instrument core drill-tap in the production of products of marine engineering, shipbuilding, ship repair power plants made of hard materials showed a high efficiency of the proposed technology for the processing of high-quality small-diameter threaded holes that meet modern requirements.